STABILITY IN ORTHOGNATHIC SURGERY IN CLASS III PATIENTS (International Seven Journal of Multidisciplinary, 2026)
Skeletal Class III malocclusion represents a complex dentofacial deformity characterized by discrepancies between the maxillary and mandibular skeletal bases, with significant aesthetic, functional, and psychosocial repercussions. In adult patients, bimaxillary orthognathic surgery has been widely recognized as the standard treatment for the definitive correction of these alterations; however, postoperative skeletal stability remains one of the main clinical challenges, as relapse may compromise the results achieved in the medium and long term. This study aimed to review recent literature on postoperative stability in Class III patients undergoing orthognathic surgery, with emphasis on factors associated with bone and condylar adaptation, three-dimensional planning, and clinical implications for maintaining outcomes. This is a narrative literature review based on studies published in recent years (2022 to 2025) addressing biomechanical, articular, and technological aspects related to orthognathic surgery. The findings demonstrate that bimaxillary surgery promotes significant improvements in facial aesthetics, skeletal symmetry, occlusion, and quality of life. Maxillary positioning and fixation show greater predictability compared to the mandible due to several factors. Postoperative stability is multifactorial and influenced by the magnitude of surgical movements, temporomandibular joint adaptation, neuromuscular response, and the use of three-dimensional virtual planning. Although the incidence of condylar resorption in Class III patients is lower than that observed in other skeletal deformities, this condition remains clinically relevant. It is concluded that bimaxillary orthognathic surgery, when properly indicated, planned, and performed, constitutes an effective and highly stable approach for the treatment of skeletal Class III, surpassing orthodontic camouflage in cases with significant skeletal discrepancy.